Rate of glycemic control and associated factors among type two diabetes mellitus patients in Ethiopia: A cross sectional study - Nigussie, Shambel; Birhan, Nigussie; Amare, Firehiwot; Mengistu, Getnet; Adem, Fuad; Abegaz, Tadesse Melaku (PloS one, 2021)
To assess the rate of glycemic control and associated factors among type 2 diabetes mellitus patients at Dilchora Referral Hospital, Dire Dawa, Eastern Ethiopia. A cross-sectional study was conducted from 13 May to 16 August 2019. Type 2 diabetic patients on follow up at Dilchora Referral Hospital who fulfilled the inclusion criteria of the study were included. Systematic random sampling was used to select study participants. Data was collected by a face-to-face interview and review of medical records. The primary outcome was the level of blood glucose during three consecutive visits. Poor glycemic control was defined as a blood sugar level of more than 154 mg/dL based on the average of measurements from three consecutive visits. Multivariate logistic regression analysis was used to identify determinants of glycemic control. A total of 394 participants responded to the interview and were included in the final analysis. The overall prevalence of poor glycemic control was 45.2% (95%CI: 40.6%-50.0%). Patients who were on oral anti-diabetic drug plus insulin had more than two times greater chance of poor glycemic control than patients on oral anti-diabetic drug alone: 2.177(95%CI:1.10-4.29). The odds of poor glycemic control in patients who did not understand the pharmacist's instructions was two times higher than patients with good understanding of instructions 1.86(95%CI: 1.10-3.13). Patients who had poor level of practice were found to have poor glycemic control: 1.69(95% CI: 1.13-2.55). The overall prevalence of poor glycemic control was high among type 2 diabetes patients. Oral anti-diabetic drugs in combination with insulin, lack of understanding of pharmacist's advice, and poor practice of diabetic patients were significant factors of poor glycemic control. Pharmacists should reassure the understanding of patients before discharge during counseling. Optimization of the dose of antidiabetic medications and combination of oral hypoglycemic agents should be considered.